WALLABY early science − V. ASKAP H i imaging of the Lyon Group of Galaxies 351. Issue 4 (7th September 2019) - For, B-Q; Staveley-Smith, L; Westmeier, T; Whiting, M; Oh, S-H; Koribalski, B; Wang, J; Wong, O I; Bekiaris, G; Cortese, L; Elagali, A; Kleiner, D; et al.
ABSTRACT: We present an H i study of the galaxy group LGG 351 using Widefield ASKAP L -band Legacy All-sky Blind Survey (WALLABY) early science data observed with the Australian Square Kilometre Array Pathfinder (ASKAP). LGG 351 resides behind the M 83 group at a velocity range ( cz ) of ∼3500–4800 km s −1 within the rich Hydra-Centaurus overdensity region. We detect 40 sources with the discovery of a tidally interacting galaxy pair and two new H i sources that are not presented in previous optical catalogues. 23 out of 40 sources have new redshifts derived from the new H i data. This study is the largest WALLABY sub-sample to date and also allows us to further validate the performance of ASKAP and the data reduction pipeline askapsoft . Extended H i emission is seen in six galaxies indicating interaction within the group, although no H i debris is found. We also detect H i in a known ultra-faint dwarf galaxy (dw 1328−29), which demonstrates that it is not a satellite of the M 83 group as previously thought. In conjunction with multiwavelength data, we find that our galaxies follow the atomic gas fraction and baryonic Tully–Fisher scaling relations derived from the GALEX Arecibo SDSS Survey. In addition, majority of our galaxies fall within the star formation main sequence indicating inefficiency of gas removal processes in this loose galaxy group.